The Relationship between Living Environment and Life Satisfaction in Residents of Rasht City, North of Iran - Abolfazl Etebarian Khorasgani; Atefeh Ghanbari Khanghah; Ezzat Paryad; Zahra Atrkar Roshan; Enayatollah Homaei Rad (Guilan University of Medical Sciences, 2021)
Introduction: Life satisfaction reflects an individualchr('39')s overall feelings about life, influenced by various factors. Objective: This study aimed to identify and introduce the indices related to the living environment that affect life satisfaction. Materials and Methods: This study was performed on 1000 residents of 55 neighborhoods of Rasht City (north of Iran) by an analytical cross-sectional method. The participants were chosen with a multistage cluster sampling method. The study data were collected using questionnaires, including the residentschr('39') characteristics, indicators of the living environment, and the satisfaction with life scale. The obtained data were analyzed using descriptive statistics, and inferential statistics, including the Pearson correlation coefficient, independent t test, analysis of variance, and linear regression. Results: Based on the present study results, the mean±SD age of the subjects in the study was 43.73 ±15.55 years. The analysis showed that their level of life satisfaction was average mean ±SD: 19.41 ±7.63, range: 5-35). The regression analysis identified dissatisfaction of facilities (B= -0.366; 95%Cl : -0.434, -0.298; P= 0.001), satisfaction with living in the local area (B= 0.248; Cl: 0.123,  0.373; P= 0.001), duration of residence (B: -0.364;95% Cl: -0.625, -0.102; P= 0.006) and gender (women compared to men) (B: 0.896; Cl: 0.011,   1.781;  P=0.047) as the predictors of life satisfaction. Conclusions: According to the results, the life satisfaction of our study participants was at a moderate level and was affected by living environment indicators, especially facilities.